2015
DOI: 10.14257/ijmue.2015.10.1.4
|View full text |Cite
|
Sign up to set email alerts
|

What Affect Lower Grade Learner's Perceived Usefulness and Perceived Ease of Use of Mobile Digital Textbook Learning System? An Empirical Factor Analyses Investigation in China

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Pedagogical processes can also be carried out in full or partly with mobile technologies (Oran & Karadeniz, 2007) thereby increasing lifelong learning in both formal and informal educational settings . This goes to prove that mobile learning technology offers the potential for improved teaching and learning (Shen, Luo, & Sun, 2015). It is also worthy of note that the size of these mobile devices have made it widely accepted particularly by learners who are always on the move (Sharples, Taylor, & Vavoula, 2005).…”
mentioning
confidence: 98%
“…Pedagogical processes can also be carried out in full or partly with mobile technologies (Oran & Karadeniz, 2007) thereby increasing lifelong learning in both formal and informal educational settings . This goes to prove that mobile learning technology offers the potential for improved teaching and learning (Shen, Luo, & Sun, 2015). It is also worthy of note that the size of these mobile devices have made it widely accepted particularly by learners who are always on the move (Sharples, Taylor, & Vavoula, 2005).…”
mentioning
confidence: 98%
“…Since the late 1990s, as belief variables in technology acceptance model is too simple, and that the limitation of being measured as a single item is perceived, extended studies by revising model or introducing various factors have been proposed (Venkatesh, 2000;Choi, 2012). And Davis et al (1992), and Shen et al (2015) suggested the technology acceptance model that perceived availability and perceived ease of use effect directly on behavioral intention, except for attitude variables (Davis, 1992;Shen et al, 2015). Also, this model suggested factors that can affect perceived availability social influences or work-relatedness and cognitive tools such as image and quality, and factors that can affect perceived ease of use are self-efficacy and anxiety about technology, curiosity, interest and pleasure.…”
Section: Theoretical Background Of Researchmentioning
confidence: 98%
“…The department has no remarkable impact on students' gratification level [25,26]. Some studies show that there is no considerable relationship between gender [27,28] or age [23,24] and students' perceived usefulness. However, the latter is disputable [29].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Τhe students' grades have a significant effect on perceived usefulness [24,25], but not the department [25,30]. There is no substantial difference between male and female students' perceived ease of use [27,28]. However, age has a significant impact [29,31] and there is a remarkable effect of students' grades [24,25].…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation